JOB CRAFTING ANTECEDENTS AND CONSEQUENCES: A LITERATURE REVIEW - Nesimnasi, Sarce A.R (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: The organization always strives to improve its employees' ability to continue to be better; employees are required to be effective and efficient and develop every talent and potential. Methods: To analyze the research, this paper conducted a literature review on selected publications. Results: Job Crafting is an employee technique that adjusts the qualities of the job, either physically or cognitively, depending on the employees' preferences, abilities, and needs, thereby making the work done becomes more meaningful. Conclusion and suggestion: Job crafting is the skills of employees who are able to redesign their work on their own initiative, with or without management involvement hence that the work carried out by employees feels easier and more comfortable because there is a balance between demands and work resources with personal abilities or employee needs.